2001
DOI: 10.1046/j.1471-4159.2001.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of adenosine A2 receptor agonist and antagonist on neuronal and astrocytic intermediary metabolism studied with ex vivo13C MR spectroscopy

Abstract: C]GABA in the DMPX group compared to control and an increase in the total amount of taurine in both treatment groups was detected. The present study shows that A 2 receptor agonist and antagonist have similar effects; however, in cortex GABAergic neurones and astrocytes were affected in contrast to subcortex, where glutamatergic neurones showed the greatest changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In the extracellular space ATP can be converted to adenosine by the dephosphorylating action of the ectonucleotidase anchored at the plasma membrane (Joseph et al, 2003). Adenosine can activate adenosine receptors and therefore modulate neuronal activity by triggering K + efflux (e.g., Newman, 2003), as well as intermediary metabolism (Haberg et al, 2000; Hammer et al, 2001; Duarte et al, 2016) and blood flow (Blood et al, 2003; Iliff et al, 2003; Gordon et al, 2008). D-serine that can be released from astrocytes was also shown to modulate electrical neurotransmission by acting at the glycine binding site of NMDA receptor (Stevens et al, 2003).…”
Section: Functions Of Astrocytes In the Brainmentioning
confidence: 99%
“…In the extracellular space ATP can be converted to adenosine by the dephosphorylating action of the ectonucleotidase anchored at the plasma membrane (Joseph et al, 2003). Adenosine can activate adenosine receptors and therefore modulate neuronal activity by triggering K + efflux (e.g., Newman, 2003), as well as intermediary metabolism (Haberg et al, 2000; Hammer et al, 2001; Duarte et al, 2016) and blood flow (Blood et al, 2003; Iliff et al, 2003; Gordon et al, 2008). D-serine that can be released from astrocytes was also shown to modulate electrical neurotransmission by acting at the glycine binding site of NMDA receptor (Stevens et al, 2003).…”
Section: Functions Of Astrocytes In the Brainmentioning
confidence: 99%
“…Since adenosine is a by-product of adenosine monophosphate resulting from acetate metabolism, it was suggested that its production should increase in the brain following acetate administration as previously found in both liver and heart (Kiviluoma et al 1989;Campisi et al 1997). However it was recently shown that no adenosine could be detected after cerebral acetate metabolism (Haberg et al 2000;Hammer et al 2001). Potential short-term effects of acetate infusion on brain metabolism remain to be investigated in more detail.…”
Section: Physiological Effects Of Acetatementioning
confidence: 99%
“…1). Apart from these predominant synaptic effects, it has also been reported that A 2A R can impact on neuronal metabolism [92] but the functional relevance of this finding remains to be explored. Finally, A 2A R are also located in astrocytes and microglia cells [68,93], where they control the uptake of glutamate [94] and the expression of cytokines [68,93].…”
Section: B Adenosine a 2a Receptor Neuromodulation Systemmentioning
confidence: 99%